Neonatal neuroimaging after repair of congenital diaphragmatic hernia and long-term neurodevelopmental outcome. Issue 3 (5th September 2019) - Gunn-Charlton, Julia Kate; Burnett, Alice C; Malarbi, Stephanie; Moran, Margaret M; Hutchinson, Esther A; Greaves, Susan; Hunt, Rod W
Abstract : Objective: Previous outcome reports of congenital diaphragmatic hernia (CDH) have described neuroimaging anomalies and neurodevelopmental impairment. However, the link between imaging and outcome has not been described. We aimed to determine whether routine postoperative neonatal neuroimaging in infants with CDH detects later neurodevelopmental impairment. Methods: In a prospective cohort study within a clinical service in The Royal Children's Hospital Newborn Intensive Care. Cerebral ultrasound was performed in 81 children and MRI in 57 children who subsequently underwent neurodevelopmental follow-up after surgery for CDH. MRI scans were analyzed using a scoring system designed to identify injury, maturation and volume loss. Neurodevelopmental assessment occurred at 2 years (48) and neurocognitive assessment at 5 years (26) and/or 8 years (27). Brain imaging scores corrected for gestational age at scan time were correlated with outcome measures, adjusting for known clinical confounders. Results: Clinically significant findings were identified on MRI of 16 (28%) infants. Mean scores were in the normal range for all domains assessed at each age. Language impairment was seen in 23% at 2 years and verbal intellectual impairment in 25% at 8 years. Mean cognitive scores were lower in 2-year-old children with white matter injury on MRI (p=0.03). Mean motor scores were lower in 2-year-old children with brain immaturity (p=0.01). Associations between MRI and 5-year and 8-year assessments were no longer significant when adjusting for known clinical confounders. Conclusions: Neuroimaging abnormalities were associated with worse neurodevelopment at 2 years, but not with later neurocognitive outcomes, after accounting for clinical risk factors.